Antidiabetic Effects of Aerobic Exercise and Bitter Melon Powder Supplementation in Type 2 Diabetic Females - K Azali Alamdari; J Bashiri; S Tahmasebi (Institue of Medicinal Plants, ACECR, 2016)
Background: The process of diabetes control involves a mixture of dietary, pharmacological and physical exercise interventions as therapeutic methods. However there is a considerable risk of hypoglycemia incidence with synchronized supplementation of bitter melon and physical exercise and also the antihyperlipidemic effects of bitter melon was not fully elucidated. Objective: The aim was to investigate the synchronized effects of aerobic training and bitter melon powder supplementation on metabolic control in type II diabetic female patients (Age: 56.89±7.48 yrs. Weight: 78.75±5.56 kg and Height: 164.54±6.71 cm). Methods: Following to baseline FBS, 2hpp, HbA1c (A1C), HDL, LDL, TG and TC measurements, the subject were randomized into four groups (N=12): Control, Bitter melon, Exercise and Bitter melon-Exercise. The Bitter melon and Control groups received supplement/placebo containing capsules for eight weeks (three meals per day) with dosage of eight mg/kg.bw in a double blind order. The Exercise groups were run on a treadmill at moderate intensity, three sessions per week during this period. Results: Fasting glucose was decreased in Bitter melon, Exercise and Bitter melon-Exercise groups (P<0.05), however there were no between group differences in the amount of deceases (P>0.05). A1C was also decreased in these three groups with sharp decreases in Bitter melon-Exercise group (P<0.05). The 2hpp, HDL, LDL, TG and TC levels were only decreased in Exercise groups (P<0.05). Conclusion: Bitter melon supplementation along with exercise training in accompany with other therapeutic proceedings, could provide sharper decreases in A1C level in well controlled patients as the most important index for diabetes control. However; the merely supplementation with bitter melon has no significant effect on blood lipids.